Dual Circularly Polarized Metasurface Antenna Based on Inward and Outward Surface Wave Duplexing - Thanikonda, Ravikanth; Faenzi, Marco; Toccafondi, Alberto; Martini, Enrica; Maci, Stefano (IEEE transactions on antennas and propagation, 2025)
This article proposes the design and numerical validation of a dual-polarized metasurface (MTS)-based antenna, in which the two polarizations share the same circular aperture. The design exploits the interaction of duplexed inward- and outward-traveling surface waves (SWs) with an unwinding spiral MTS impedance pattern. The two inward/outward illuminations share a common radiating aperture and are originated by an integrated triaxial-cable feeding. The inward cylindrical wave is launched in a parallel plate waveguide (PPWG) by the external part of the triaxial cable (TC) and then redirected inward by a corner reflector at the aperture rim. Interacting with the anisotropic-modulated impedance boundary condition (IBC), it provides a broadside left-handed circularly polarized (LHCP) beam. On the other hand, the outward SW originates from the center as excited by a monopole connected to the inner conductor of the TC and provides a right-handed circularly polarized (RHCP) broadside radiation. New design formulas are derived for the total efficiency of the two modes. A practical feeding structure is designed and validated, featuring a coplanar-to-triaxial waveguide transition for broadband performance, ensuring a low-profile and simple configuration.